INJEKSI FOAM SEBAGAI TERTIARY OIL RECOVERY - Iwan Setya Budi; Agus Rudiyono; Astra Pramana Astra Pramana (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
Foam injection is a variance of gas flood as tertiary recovery method designed to mitigate low sweep efficiency normally found in gas flood due to inheritance of density difference between injected gas and oil which often severed by presence of reservoir heterogeneity (permeability contrast in this case). Foam EOR has two goals: (1) improve oil recovery by promoting better sweep efficiency, and (2) reduce carbon emission related to global warming issue provided that the injectant gas used is CO2, hydrocarbon gas or flue gas.. Reservoir simulation performed is able to show recovery improvement of foam compared to continuous gas injection.